2021
DOI: 10.1007/s10482-021-01673-w
|View full text |Cite
|
Sign up to set email alerts
|

Genome analysis of alginate synthesizing Pseudomonas aeruginosa strain SW1 isolated from degraded seaweeds

Abstract: Pseudomonas aeruginosa strain SW1 is an aerobic, motile, Gram-negative, and rod-shaped bacterium isolated from degraded seaweeds. Based on the 16S rDNA sequence and MALDI TOF analysis, the strain SW1 exhibits 100% similarity with P. aeruginosa DSM 50071, its closest phylogenetic neighbour. P. aeruginosa is an opportunistic pathogen that can infect plants, animals and humans. The complete genome of P. aeruginosa strain SW1 consists of a single circular chromosome with 23,258,857 bp (G+C content of 66%), includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 67 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…All of these steps have been previously identified and characterized in many reviews [42,69,70] and the biosynthesis of alginate has been shown to be extremely similar for both Pseudomonas aeruginosa and Azotobacter vinelandii, resulting from a complex regulatory network of proteins [41,51,59,65]. In P. aeruginosa, a 12-gene operon is strictly controlled by algD transcription, the first gene of the alginate biosynthetic operon [53,71], and two additional internal promoters upstream of algG and algI [72] (Figure 1). Three transcription promoter regions have been described for the algD operon, namely algDp1 (δ D promoter, algDp2 (AlgU-δ E promoter), and algDp3 [65].…”
Section: Overview Of the Genetics And Regulation Of Bacterial Alginat...mentioning
confidence: 95%
“…All of these steps have been previously identified and characterized in many reviews [42,69,70] and the biosynthesis of alginate has been shown to be extremely similar for both Pseudomonas aeruginosa and Azotobacter vinelandii, resulting from a complex regulatory network of proteins [41,51,59,65]. In P. aeruginosa, a 12-gene operon is strictly controlled by algD transcription, the first gene of the alginate biosynthetic operon [53,71], and two additional internal promoters upstream of algG and algI [72] (Figure 1). Three transcription promoter regions have been described for the algD operon, namely algDp1 (δ D promoter, algDp2 (AlgU-δ E promoter), and algDp3 [65].…”
Section: Overview Of the Genetics And Regulation Of Bacterial Alginat...mentioning
confidence: 95%
“…In the outer membrane, the cell of P. aeruginosa includes virulence factors such as lipopolysaccharide (LPS) [ 30 ]. The main feature of this bacteria is the capability to produce biofilms rich in alginates [ 31 , 32 , 33 , 34 , 35 ]. In Pseudomonas aeruginosa , alginate is polymerized and secreted by a specific unit that spans the outer and inner membranes of the bacteria [ 36 , 37 ].…”
Section: Alginate Extraction and Originmentioning
confidence: 99%